(Mis)Appropriated Liberty: Identity, Gender Justice, and Muslim Personal Law Reform in India - Choudhury, Cyra Akila (Columbia Journal of Gender and Law, 2008)
Muslim women in India often find themselves caught between loyalties to their religious or ethnic communities and a desire for greater freedom and equality as women within those communities. They face significant constraints in reconciling these conflicting influences, and a great many of them do it in the context of poverty. As Zoya Hasan notes, “Muslim women are triply disadvantaged-as members of a minority, as women, and most of all as poor women.” On one hand, traditionalists within Muslim communities in India seek to universalize and ossify interpretations and practices of Islam that maintain women’s status as second-class members with far fewer rights than men. Resistance to conservative interpretations of Islam is cast as disloyalty and can call into question the very identity of a Muslim woman within her community. On the other hand, loyalty to religious interpretations and to principles that are clearly gender-biased calls into question Muslim women’s commitment to emancipation and gender justice. These experiences are exacerbated for women who are economically impoverished.